Technological and chemical characteristics of spurdog Squalus boretzi - L. V. Shulgina; E. V. Yakush; К. G. Pavel’; E. A. Solodova; I. V. Maltsev (Известия ТИНРО)
Safety indices, size-weight structure, and chemical composition of the muscle tissue and liver are determined for a small-sized shark species as spurdog Squalus boretzi caught with longline in the area of Imperial Ridge seamounts (North-West Pacific). The highest catch was recorded on Koko Rise at the depth of 700 m. The sharks had the body length from 55 to 94 cm and the weight of 830–4540 g. Content of proteins and lipids in the muscle tissue (24.8 % and 0.8 %, respectively) of spurdog corresponds to low-calorie high-protein fish. The proteins contain all the essential amino acids in the ratio close to an «ideal protein». The lipids are presented by mainly phospholipids (57 % of total amount). The portion of polyunsaturated fatty acids in the lipids is 46.6 %, including 36.9 % of omega-3 fatty acids. The sum of biologically significant fatty acids (eicosapentaenoic and docosahexaenoic) reaches 34.7 %. The shark liver contains about 83 % of lipids, mostly monounsaturated fatty acids (53 % of total lipid amount) and 20.6 % of PUFA. The amount of biologically significant fatty acids (EPA + DHA) in the liver is about 10.5 %. In terms of hygienic and microbiological parameters, the muscle tissue of Squalus boretzi meets the requirements of Euro-Asian Union (№ 040/2016) and Customs Union (№ 021/2011). However, a heightened content of mercury is found in the liver of spurdog that makes difficult to use this source of valuable lipids.